Heat and mass transfer in quenching the reaction of thermal decomposition of a forest combustible material with a group of water drops; Journal of Engineering Physics and Thermophysics; Vol. 87, iss. 3 - Kuznetsov G. V. Geny Vladimirovich (2014, 2014)
Title screen